Increased T regulatory cells are associated with adverse clinical features and predict progression in multiple myeloma - Muthu Raja, Karthick Raja; Rihova, Lucie; Zahradova, Lenka; Klincova, Maria; Penka, Miroslav; Hajek, Roman (PloS one, 2012)
BACKGROUND: Regulatory T (Treg) cells play an important role in the maintenance of immune system homeostasis. Multiple myeloma (MM) is a plasma cell disorder frequently associated with impaired immune cell numbers and functions. METHODS: We analyzed Treg cells in peripheral blood (n = 207) and bone marrow (n = 202) of pre-malignant and malignant MM patients using flow cytometry. Treg cells and their subsets from MM patients and healthy volunteers were functionally evaluated for their suppressive property. A cohort of 25 patients was analyzed for lymphocytes, CD4 T cells and Treg cells before and after treatment with cyclophosphamide, thalidomide plus dexamethasone (CTD). RESULTS: We found elevated frequencies of Treg cells in newly diagnosed (P<0.01) and relapsed MM patients (P<0.0001) compared to healthy volunteers. Also, Treg subsets including naïve (P = 0.015) and activated (P = 0.036) Treg cells were significantly increased in MM patients compared to healthy volunteers. Functional studies showed that Treg cells and their subsets from both MM and healthy volunteers were similar in their inhibitory function. Significantly increased frequencies of Treg cells were found in MM patients with adverse clinical features such as hypercalcemia (>10 mg/dL), decreased normal plasma cell (≤5%) count and IgA myeloma subtype. We also showed that MM patients with ≥5% of Treg cells had inferior time to progression (TTP) (13 months vs. median not reached; P = 0.013). Furthermore, we demonstrated the prognostic value of Treg cells in prediction of TTP by Cox regression analysis (P = 0.045). CTD treatment significantly reduced frequencies of CD4 T cells (P = 0.001) and Treg cells (P = 0.018) but not Treg cells/CD4 T cells ratio compared to pre-treatment. CONCLUSIONS: Our study showed immune deregulation in MM patients which is evidenced by elevated level of functionally active Treg cells and patients with increased Treg cells have higher risk of progression.
Keywords: Thalidomide; referenční hodnoty; dexamethason; proporcionální rizikové modely; Humans; Case-Control Studies; lidé středního věku; Proportional Hazards Models; Disease Progression; studie případů a kontrol; Predictive Value of Tests; Multiple Myeloma; Female; Aged; dospělí; Hypercalcemia; senioři; lidé; mnohočetný myelom; T-Lymphocyte Subsets; Adult; ženské pohlaví; CD4-Positive T-Lymphocytes; Male; Middle Aged; prediktivní hodnota testů; Dexamethasone; Aged, 80 and over; Cyclophosphamide; CD4-pozitivní T-lymfocyty; regulační T-lymfocyty; Reference Values; senioři nad 80 let; progrese nemoci; T-Lymphocytes, Regulatory; mužské pohlaví; cyklofosfamid; hyperkalcemie; T-lymfocyty - podskupiny; thalidomid